Chronobiological changes induced by the gallium complex C(24) in some hematological parameters in rats - Gârban Zeno; Ioniţă Hortensia; Gârban Gabriela; Baltă Cornel; Ahmadi-Vincu Mirela; Muselin Florin; Lungu Camelia; Acatincăi Stelian; Újhelyi Róbert; Simiz Eliza; Boldura Oana-Maria; International Symposium on Analytical and Environmental Problems (24.) (2018) (Szeged) (2018)
In the present research the authors proposed to monitor possible chronobiological changes in some hematological parameters (erythrocytes, leukocytes and thrombocytes) of Wistar strain rats induced by the novel gallium complex - C(24). For this purpose a morning (m) and an evening (e) animal series were designed, each including a control (Cp) and an experimental (E) group. Animals of the control groups (Cp-m, Cp-e) were injected intraperitoneally with polyethylene glycol and those from the experimental groups (E-m, E-e) with the novel gallium complex in the morning and in the evening. At 48 hours after the administration of substances the animals were anesthetized and blood samples were collected for biochemical and hematological analysis. Erythrocytes, leukocytes and thrombocytes parameters were determined. The resulted values showed an increase in most of erythrocytes parameters in E-m group and a slight decrease of all parameters in E-e group. As to leukocytes parameters an increase of most values both in E-m and E-e groups was recorded. Platelets parameters indicated decrease both in E-m and E-e groups, being more evident in case of platelets number.